Experiences in district’s countryside (2008)
By taking professional practice as an option grade, it came to support the project Productive and Healthy Peasant Housing (Vivienda Campesina Productiva y Saludable) of the SDDE work was done in Usme and Sumapaz making proposals for the construction and improvement of housing, including alternative productive spaces. This made possible to know peasant communities from the Urban Edge and Protected Areas who propose the social control of territory and sustainability as major themes. The weaknesses in community projects and the non-recognition of alternative technologies in the housing subsidy policies create a need for support that academic and institutionality can provide.